Crystallographic Investigation and Selective Inhibition of Mutant Isocitrate Dehydrogenase - Zheng, Baisong (American Chemical Society, 2013)
[Image: see text] Mutations in isocitrate dehydrogenase (IDH), a key enzyme in the tricarboxylic acid cycle, have recently been found in ∼75% glioma and ∼20% acute myeloid leukemia. Different from the wild-type enzyme, mutant IDH1 catalyzes the reduction of α-ketoglutaric acid to d-2-hydroxyglutaric acid. Strong evidence has shown mutant IDH1 represents a novel target for this type of cancer. We found two 1-hydroxypyridin-2-one compounds that are potent inhibitors of R132H and R132C IDH1 mutants with K(i) values as low as 120 nM. These compounds exhibit >60-fold selectivity against wild-type IDH1 and can inhibit the production of d-2-hydroxyglutaric acid in IDH1 mutated cells, representing novel chemical probes for cancer biology studies. We also report the first inhibitor-bound crystal structures of IDH1(R132H), showing these inhibitors have H-bond, electrostatic, and hydrophobic interactions with the mutant enzyme. Comparison with the substrate-bound IDH1 structures revealed the structural basis for the high enzyme selectivity of these compounds.